Description Of Sports Behavior In Diabetes Mellitus Patients At UPT Puskesmas Delitua Year 2021 - Mestiana Br. Karo; Lindawati Tampubolon; Mardiati Barus; Annastasya Paulina Br. Ginting (Sean Institute, 2022)
Diabetes Mellitus (DM) is a chronic metabolic disorder that is better known as the silent killer of humans. Often humans do not realize that the person has diabetes, and often experience delays in handling it so that many complications occur. Diabetes is also known as the